A film coating assembled by tubular nitrogen-doped carbon fibers as an efficient membrane spacer to suppress the shuttle effect for long-life lithium–sulfur batteries. (1st January 2021) - Han, Kairu; Wang, Ting; Zhang, Na; Zhang, Weimin; Ge, Wenqing; Xie, Gang; Zhang, Lipeng; Zhang, Tiezhu
Highlights: The hollow structured one-dimensional tubular nitrogen doped carbon fibre (TNCF) was obtained by pyrolyzing the tubular polypyrrole (PPy). TNCF has a hollow tubular structure with a rough surface. The porous hollow carbon structure plays an important role in the adsorption of polysulfides and can better limit the diffusion and transfer of soluble polysulfides. TNCF coating can effectively hinder the diffusion of polysulfides and TNCF coating modified separator is a promising high-performance lithium-sulfur battery high-performance separator. Abstract: Exploiting effective protocols to suppress the lithium polysulfide shuttling effect is critical to achieve a long life for lithium–sulfur (Li–S) batteries. Here we demonstrate a laminated separator which was obtained by coating a layer of tubular nitrogen doped carbon fibre (TNCF) on PP/PE/PP separator with an expect to alleviate such a problem. The hollow structured one-dimensional TNCF was obtained by pyrolyzing the tubular polypyrrole (PPy) which was synthesized through an auto-degradable template method. And the laminated separator was prepared by a simple vacuum-assisted filter method. Due to enhancement of the electrical conductivity and the chemisorption with lithium polysulfides, we observed that the rate performance and the cyclability of the Li–S battery were remarkably enhanced when the TNCF separator was used. The capacity decay rate were determined to be 0.13% and 0.33% per cycle upon 200 cycles at 0.5 C for the Li–S batteries with the TNCF coated and the un-coated separators, respectively. That present the TNCF coated separator a promising high performance separator for long-life Li–S batteries. Graphical abstract: Image, graphical abstract